ECTHR_COMMITTEE 57628/09 vom 14. März 2013 , AFFAIRE X-CODE LYSEIS PLIROFORIKIS A.E. c. GRÈCE - Ecthr Committee (2013)
Violation de l'article 6 - Droit à un procès équitable (Article 6 - Procédure civile;Article 6-1 - Délai raisonnable); Violation: 6;6-1